Análise espaço-temporal do uso e ocupação do solo e simulação dos processos hidrossedimentológicos no bioma cerrado: o caso da bacia do Rio das Almas, Goiás - Fonseca, Cláudia Adriana Bueno da (2020)
The change in land use and occupation has caused changes in the fluvial dynamics and hydrosedimentological regime in the Rio das Almas watershed, located in the Cerrado biome in the state of Goiás. These manifestations have been occurring at an accelerated rate since the 1990s due to the pressure of agribusiness by the demand for food grains, sugar cane and cattle breeding. The seriousness of the problem is confirmed when one analyzes the data on deforestation and the advance of new temporary crops in the basin, which can affect natural factors such as: water production, soil quality, increased runoff, soil loss, and sediment production. In this sense, the objective of this work is to analyze the spatial-temporal changes of land use and occupation and their influence on hydrosedimentological processes in the Almas river basin, in the period between 1991 and 2017. This watershed has a relevance in water production and electricity generation. To conduct this study, Landsat 5 and Landsat 8 satellite images from the dates 06/13/1991 and 06/13/2017 were used. The SWAT model was applied from 01/01/1974 to 12/31/1980 (already including the three years of model warming) and validation occurred from 01/01/1981 to 12/31/1994, with the following products: (a) 1991 land use, (b) soil type map, (c) digital elevation model (DEM) and (d) meteorological and hydrological data (1974-1994). For the study, two distinct hypothetical land use scenarios simulated in the model over the period 1974-1994 were defined: (a) Scenario 1: considered optimistic, a scenario that recommends the sustainable use and preservation of natural vegetation, emphasizing the restoration of essential ecological processes connected to riparian corridors, springs and hilltops and hillsides that were occupied by anthropic activities (agriculture, livestock and urban area), mapped in the 2017 land use; and (b) Scenario 2: considered pessimistic, which presents a scenario of increased deforestation and expansion of farming activities. The results obtained in the calibration and validation of the model for the fluviometric stations (Jaraguá and Colônia dos Americanos) indicated a very good performance with values of R2 = 0,80 and NS = 0,61; and R2 = 0,85 and NS = 0,82, respectively. The observed average monthly flow rate for Jaraguá station was 35,44 m3/s and the simulated 41,48 m3/s (17% difference). For the Colônia dos Americanos station the average observed flow was 337,80 m3/s and the adjusted one was 360,60 m3/s (difference of 6,75%). The average estimate of sediment yield was 48,17 ton/ha.year in the analyzed period (1974-1994). The difference between the 1991 average adjusted land use flow rate and the simulated one for Scenario 1 was 95,27 m3/s, this is equivalent to variation of 26,42% and for Scenario 2 the difference was 139,84 m3/s (equivalent to variation of 38,78%). With respect to the hypothetical land use scenarios, the estimate of sediment volume produced in the optimistic scenario had a significant reduction of 10,96% in relation to the 1991 land use (calibrated in the model) and of 35,19% compared to the pessimistic scenario. On the other hand, the pessimistic scenario presented a high sediment production of 54,29% when compared to the optimistic scenario, and in relation to the 1991 soil use it had an increase of 37,37%. As for the projection of the hypothetical pessimistic scenario, the results demonstrated that the basin has a greater predisposition for soil loss and sediment production in the sub-basins with alterations in vegetation cover, soils prone to water erosion, agricultural land use and with greater rainfall intensity.